Engendering Trade - Do, Quy-Toan (Washington, DC: World Bank, 2012)
The authors analyze the interaction between a country's world market integration and its attitude towards gender roles. They discuss both theoretically and empirically how female empowerment is a source of comparative advantage that shapes a country's response to trade opening. Reciprocally, the authors show that as countries integrate into the world economy, the costs and benefits of gender discrimination shift. Their theory goes beyond a potential aggregate wealth effect associated with trade opening, and emphasizes the heterogeneity of impacts. On the one hand, countries in which women are empowered--measured by fertility rates, female labor force participation or female schooling--experience an expansion of industries that use female labor relatively more intensively. On the other hand, the gender gap is smaller in countries that export more in relatively femalelabor intensive sectors. In an increasingly globalized economy, the road to gender equality is paradoxically very specific to each country's productive structure and exposure to world markets.